A Study on the Relationship Between Grammar Proficiency and Oral Communication Performance of Intensive English Course Participants - Aini, Devi Nur (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
This study examines the relationship between grammar proficiency of the students who have finished an intense English course and the growth of their speaking abilities. The purpose of the study is to ascertain whether oral communication ability is enhanced by a greater degree of grammatical understanding. 51 students from an intense English program at one of the state university in Indonesia participated in a quantitative correlational research design. A grammar competency test and a speaking performance evaluation using standardized rubrics with an emphasis on coherence, accuracy, and fluency were used to gather data. The results showed a high positive link between speaking ability and grammar mastery, suggesting that pupils who are more proficient in grammar typically do better while speaking. The findings imply that in order to improve students' overall language proficiency, communicative speaking exercises and explicit grammar teaching should be combined. This study advances our knowledge of how oral skill development in intense language learning environments is supported by grammatical knowledge.